Evaluation of Red Beet Root Activity Physiologically and Histologically in Males Rats - Ibrahem Hasan Al-Kraie (Journal of Global Pharma Technology, 2020)
This research design to study the effect of cadmium chloride (Cdcl2) and red beet root juice on heart and kidney by measured the physiological parameters in the experimental male’s rats for 30days.  Twenty males rats were assigned to 4 groups each group contain 5 rats. First group was the control group (G1), the second group was cadmium chloride group (G2), third group was cadmium chloride &red beet juice (G3), than last group was red beet juice (G4). The Cd-exposure group (G2) obtained drinking a water daily containing cadmium chloride (CdCl2) in concentration of 2.0 mg Cd/L, while the G3 group treatment with red beet juice 2ml with 2ml of Cdcl2, while the last group G4 treatment with 2ml of red beet juice only.  At the end of the experimental period, blood samples were collected to determine the changes of serum Total cholesterol (TC), triglycerides (TG), high density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), very low density lipoprotein cholesterol (VLDL-C), Total protein (TP), Alanine aminotransferase (ALT), Aspartate aminotransferase (AST).  The results of the present study  indicated  that  a significantly increased  in serum  levels of TC, TG, LDL_C, VLDL_C, ALT, AST, & significant decreased  in the levels of HDL_C & TP in G2 group, while there are no significant changes of all parameters in G3&G4 group comparing with control group at Significant level (p≤0.05). Results registors also that are significantly decreased in some parameters contain T.C ,Triglycerides ,LDL_C,VLDL_C, ALT &AST concentration in G3 & G4 group ,while the results showed a significantly increased in parameters HDL_C & Total proteins comparing with G2 group that trated with cadmium chloride at Significant level (p≤0.05).  In the end of this study we find that exposure to low Cd concentration can effected on the lipid profile & lipoprotein &liver enzymes by increased this parameters, while red beet root juice treatmenting decreased that parameters.Keywords: Cadmium chloride (Cdcl2), Total cholesterol(TC), Triglycerides(TG), High density lipoprotein cholesterol (HDL_C), Low-density lipoprotein cholesterol (LDL-C), Very low density lipoprotein cholesterol (VLDL-C), Total protein(TP), Alanine aminotransferase (ALT), Aspartate aminotransferase (AST).